Crohn's Disease and Early Exposure to Thiopurines are Independent Risk Factors for Mosaic Chromosomal Alterations in Patients with Inflammatory Bowel Diseases. (9th November 2021) - Kakuta, Yoichi; Iwaki, Hideya; Umeno, Junji; Kawai, Yosuke; Kawahara, Masahiro; Takagawa, Tetsuya; Shimoyama, Yusuke; Naito, Takeo; Moroi, Rintaro; Kuroha, Masatake; Shiga, Hisashi; Watanabe, Kenji; et al.
Abstract: Background and Aims: Mosaic chromosomal alterations [mCAs] increase the risk for haematopoietic malignancies and may be risk factors for several other diseases. Inflammatory bowel diseases [IBDs], including Crohn's disease [CD] and ulcerative colitis [UC], are associated with mCAs, and patients may be at risk for haematopoietic malignancy development and/or modification of IBD phenotypes. In the present study, we screened patients with IBD for the presence of mCAs and explored the possible pathophysiological and genetic risk factors for mCAs. Methods: We analysed mCAs in peripheral blood from 3339 patients with IBD and investigated the clinical and genetic risk factors for mCAs. Results: CD and exposure to thiopurines before the age of 20 years were identified as novel independent risk factors for mCAs [odds ratio = 2.15 and 5.68, p = 1.17e-2 and 1.60e-3, respectively]. In contrast, there were no significant associations of disease duration, anti-tumour necrosis factor alpha antibodies, or other clinical factors with mCAs. Gene ontology enrichment analysis revealed that genes specifically located in the mCAs in patients with CD were significantly associated with factors related to mucosal immune responses. A genome-wide association study revealed that ERBIN, CD96, and AC068672.2 were significantly associated with mCAs in patients with CD [ p = 1.56e-8, 1.65e-8, and 4.92e-8, respectively]. Conclusions: The difference in mCAs between patients with CD and UC supports the higher incidence of haematopoietic malignancies in CD. Caution should be exercised when using thiopurines in young patients with IBD, particularly CD, in light of possible chromosomal alterations.